Apolipoprotein E ɛ2/ɛ3/ɛ4 variant in association with obstructive sleep apnoea and lipid profile: A meta-analysis. (February 2016) - Lu, Zhuoqiang; Wu, Xuemei; Jin, Xueqing; Peng, Feng; Lin, Jinxiu
Objective: A meta-analysis of the association between haplotypical variants of the apolipoprotein E ( APOE ) gene (ɛ2/ɛ3/ɛ4) and obstructive sleep apnoea (OSA) risk and changes in lipid profile. Methods: Electronic databases were searched to retrieve articles that provided data on APOE gene ɛ2/ɛ3/ɛ4 variants in patients with OSA and healthy controls. Data were extracted from eligible articles and statistical analyses were performed. Results: The meta-analysis included 14 articles involving 19 study populations (3198 patients and 6031 controls). There was no significant association between the presence of the ɛ4 allele and OSA risk. The presence of ɛ4 was associated with significantly increased total cholesterol and decreased high-density lipoprotein cholesterol, compared with ɛ4 allele negative individuals. There was a low probability of publication bias but significant heterogeneity. Conclusions: There was no association between APOE ɛ2/ɛ3/ɛ4 and OSA susceptibility. The presence of APOE ɛ4 was associated with changes in lipid profile.